Physicochemical and Sensory Evaluation of Strawberry Flavored Non-Dairy Rice Milk - Humaira, Anis; Saliza Asman (Enhanced Knowledge in Sciences and Technology, 2024)
Rice milk is a plant-based, non-dairy milk replacement prepared from rice. It is a popular selection for people who are lactose intolerant, allergic to cow’s milk, or vegan. This research provides a comprehensive investigation of the physicochemical properties and sensory characteristics of strawberry flavored non-dairy rice milk. Rice milk served as the base, providing a lactose-free and vegan alternative, with strawberry flavor added to harmonious the blend that balances the inherent sweetness of strawberries with the neutral base of rice milk. Non-dairy rice milk (F1) had the natural flavor of plant milk derived from 84% rice and sweetened with brown sugar (15%) without strawberry flavor to create a naturally mild and cameral sweet taste, whereas strawberry flavored non-dairy rice milk (F2) combined the neutral base of 76% rice milk with 17% sweet aroma and flavorful of strawberries. The texture analysis focused on four different types of textural properties, including hardness, consistency, cohesiveness, and index of viscosity, which highlight that F2 is more firm (16.02±0.71), and consistent as the pH revealed that in F2 appears to be a decrease in pH (5.36±0.10) over the three days, indicating the progression of fermentation, potentially involving the conversion of sugars to acids by microorganisms. Furthermore, F2 appears to have a little influence on protein content (1.31%), while it may lead to a reduction in total fat content (0.43%). Overall, the research shows that F2 can correspond to customer expectations and preferences.